2019
DOI: 10.5539/jel.v8n4p32
|View full text |Cite
|
Sign up to set email alerts
|

POWER UP: A Persuasive Writing Strategy for Secondary Students with Emotional and Behavioral Disorders

Abstract: In the area of written expression, students with emotional and behavioral disorders (EBD) typically perform one to two grades below their same age, non-disabled peers. Unfortunately, there is a lack of research on writing interventions to improve these outcomes. The purpose of this study was to examine the effect of a persuasive writing strategy called POWER UP to improve the quality of persuasive essays for secondary students with EBD. The results suggest that a mnemonic strategy based on the Self-Regulated S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Following quality recommendations (WWC, 2020), all studies except for two (Lavik, 2014;Lewandowski, 2011) met standards-with or without reservations-for minimum number of data points per phase and minimum number of phases. In most studies, 24 studies (57%), data collection was interrupted (i.e., no data were collected) during intervention, and baseline performance was compared with a postintervention phase (Ahn, 2017;Asaro-Saddler, 2014;Asaro-Saddler & Bak, 2012;Asaro-Saddler & Saddler, 2010;Bishop et al, 2015;Cerar, 2012;Dunn, 2012Dunn, , 2015Dunn & Miller, 2016;Evmenova et al, 2016;Garwood et al, 2019;Good, 2019;Hashey, 2015;Hoover et al, 2012;Hough et al, 2012;MacArthur & Philippakos, 2010;McKeown et al, 2015;Mong Cramer & Mason, 2014;Mourgkasi & Mavropoulou, 2018;Nordness et al, 2019;Ray et al, 2019;Saddler, 2006;Shen & Troia, 2018;Werunga, 2018). All studies except for one (Bauernschmidt, 1991) reported treatment fidelity.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following quality recommendations (WWC, 2020), all studies except for two (Lavik, 2014;Lewandowski, 2011) met standards-with or without reservations-for minimum number of data points per phase and minimum number of phases. In most studies, 24 studies (57%), data collection was interrupted (i.e., no data were collected) during intervention, and baseline performance was compared with a postintervention phase (Ahn, 2017;Asaro-Saddler, 2014;Asaro-Saddler & Bak, 2012;Asaro-Saddler & Saddler, 2010;Bishop et al, 2015;Cerar, 2012;Dunn, 2012Dunn, , 2015Dunn & Miller, 2016;Evmenova et al, 2016;Garwood et al, 2019;Good, 2019;Hashey, 2015;Hoover et al, 2012;Hough et al, 2012;MacArthur & Philippakos, 2010;McKeown et al, 2015;Mong Cramer & Mason, 2014;Mourgkasi & Mavropoulou, 2018;Nordness et al, 2019;Ray et al, 2019;Saddler, 2006;Shen & Troia, 2018;Werunga, 2018). All studies except for one (Bauernschmidt, 1991) reported treatment fidelity.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies reported IOA for other writing fluency metrics (Dunn, 2012;Lavik, 2014), and the remaining 14 studies used computer software (e.g., Microsoft Word) to determine TWW (Asaro-Saddler, 2014;Asaro-Saddler & Bak, 2012;Asaro-Saddler & Saddler, 2010;Dunn & Miller, 2016;Hashey, 2015;MacArthur & Philippakos, 2010;Mason et al, 2010Mason et al, , 2013Mong Cramer & Mason, 2014;Nordness et al, 2019;Ray et al, 2019;Regan et al, 2005;Shen & Troia, 2018;Southall, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations